Investigating Factors Influencing Social Media Performance MSMEs in JABODETABEK - Gita Megantari Novianda; So Yohanes Jimmy; Ringkar Situmorang (Eduvest - Journal of Universal Studies, 2026)
The trend of digital environmental change encourages MSMEs in Jabodetabek to utilize social media as their main marketing channel. However, not all MSMEs can optimize social media performance effectively. This study aims to analyze the factors influencing social media performance in MSMEs, focusing on the influence of environmental forces, absorptive capacity, and social media marketing capabilities in creating content (posting capability) and interacting on social media (interaction capability). This research uses a quantitative approach grounded in Resource-Based Theory (RBT) and involves respondents who are MSME owners in the Jabodetabek area. The novelty of this research lies in integrating environmental forces, absorptive capacity, and the two dimensions of social media capability—posting and interaction—into a single conceptual model. This integration provides a more comprehensive understanding of how external pressures and internal knowledge absorption work together to shape social media performance. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses. The findings reveal that environmental forces have a positive and significant influence on MSMEs’ absorptive capacity, which in turn strengthens their posting and interaction capabilities, ultimately enhancing social media performance. Theoretically, this study advances RBT by linking external factors with resource-based capabilities. Practically, it highlights the importance for MSMEs to develop strong absorptive capacity so they can transform environmental changes into effective content strategies and meaningful audience interactions, leading to improved social media performance.